ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PERBANDINGAN DI KELAS VII SMP NEGERI 4 PALU BERDASARKAN TAHAPAN PENYELESAIAN POLYA - lawaty, susy; Nurhayadi; Pathuddin (Jurnal Elektronik Pendidikan Matematika Tadulako, 2023)
This study aims to describe the types of mistakes made by students in solving comparative word problems based on the Polya stages. The subjects of this study were students of class VII Sis Al-Jufri SMP Negeri 4 Palu, totaling 3 students, namely RT, PA, and AN students. This type of research uses descriptive research with a qualitative approach. Data collection is done by tests and interviews. The results of this study indicate that students' mistakes in solving comparative word problems, especially in comparison of values ​​and comparisons of grades VII Sis Al-Jufri SMP Negeri 4 Palu, are 1) Misunderstanding of the problem (under standing the problem), namely students cannot determine what is known and what is asked in the problem, 2) Mistakes in planning a settlement plan (devise a plan), namely students cannot look for concepts or theories that support each other and look for the necessary formulas. 3) Errors in implementing the completion plan (carrying out the plan), namely students not using the steps correctly and not using procedures that are in accordance with the intent of the problem. 4) Errors in checking answers (looking back), namely students do not re-check and re-examine carefully every step of the solution taken